Effectiveness of Education on the Use of Turmeric in Efforts to Increase Immunity During Covid-19 in Preventive Efforts in RW 01 Pejaten Timur, South Jakarta - Hayati, Teti; Subiyanto, Imam (Akademi Keperawatan RSPAD Gatot Soebroto, 2022)
This study aims to determine how effective it is in providing education on the Utilization of Turmeric in Efforts to Increase Immunity During the Covid-19 Period in RW 01 Pejaten Timur, South Jakarta. Immunity is a body's immunity where if there is a decrease it will have an impact on the ease of disease entering the body, and vice versa if it increases it will not be easy for disease to enter the body. Turmeric is one type of herbal plant that is abundant in Indonesia that contains curcumin which works to increase the body's resistance or immunity, meaning that the body's defense system to fight bacteria or viruses is increased. The purpose of this study is as an education that can increase knowledge about the Utilization of Turmeric in Efforts to Increase Immunity During the Covid-19 Period. Cross Sectional research design with a quasi-experimental pretest-posttest design with one type of treatment. The results of this study show a p-value = 0.000 which is smaller than the value of α = 0.05, which means that there is an effect of providing education that can increase knowledge about the Utilization of Turmeric in Efforts to Increase Immunity During the Covid-19 Period in the Community. The conclusion is that education provided to the community increases knowledge of the Utilization of Turmeric in Efforts to Increase Immunity During Covid-19 before and after education is carried out.